2015
DOI: 10.1017/s0020818314000484
|View full text |Cite
|
Sign up to set email alerts
|

Human Rights Prosecutions and Autocratic Survival

Abstract: Do human rights prosecutions deter dictatorships from relinquishing power? Advances in the study of human rights show that prosecutions reduce repression in transition countries. However, prosecuting officials for past crimes may jeopardize the prospects of regime change in countries that have not transitioned, namely dictatorships. The creation of the International Criminal Court has further revitalized this debate. This article assesses how human rights prosecutions influence autocratic regime change in neig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…Whereas deterrence is about stopping actors from doing things they have not yet done, compellence is about stopping them from doing things they are already doing (Schelling, 1966: 72-73). Applying a deterrence logic during conflict makes sense if one is considering whether trials stop armed combatants from committing certain acts during battle (Jo & Simmons, 2016), influence autocrats' decisions to step down (Nalepa & Powell, 2015), or alter the behavior of actors in neighboring countries (Escriba-Folch & Wright, 2015). It also is logical to focus on deterrence after the conflict has terminated, when the question becomes how to prevent actors from starting a new fight.…”
Section: Judicial Interventions and The Duration Of Intrastate Conflictmentioning
confidence: 99%
“…Whereas deterrence is about stopping actors from doing things they have not yet done, compellence is about stopping them from doing things they are already doing (Schelling, 1966: 72-73). Applying a deterrence logic during conflict makes sense if one is considering whether trials stop armed combatants from committing certain acts during battle (Jo & Simmons, 2016), influence autocrats' decisions to step down (Nalepa & Powell, 2015), or alter the behavior of actors in neighboring countries (Escriba-Folch & Wright, 2015). It also is logical to focus on deterrence after the conflict has terminated, when the question becomes how to prevent actors from starting a new fight.…”
Section: Judicial Interventions and The Duration Of Intrastate Conflictmentioning
confidence: 99%
“…At the same time, party‐based regimes are more vulnerable to domestic mass protest than other regimes: As party‐based regimes often claim to serve the broader interest of the people, popular collective action can easily challenge the legitimacy of this claim (Ulfelder ) . Existing research has shown that these differences in their domestic strategies of political survival translate into differential behaviour when authoritarian regimes are targets of external interference (Escribà‐Folch & Wright , forthcoming; Morrison ; Wright ).…”
Section: China's External Relations Regime Type and Autocratic Persimentioning
confidence: 99%
“…Political elites are more likely to accept democracy and depart from power if they are not afraid of redistribution (Acemoglu & Robinson, 2006) or worried about their fate and immunity after leaving office (O'Donnell & Schmitter, 1986;Przeworski, 2015). There is also a growing literature that focuses on the negative consequences of leaving office behind (Baturo, 2014;Escriba-Folch, 2013;Escriba-Folch & Wright, 2015;Goemans, 2008). If leaders are influenced by the expected losses after departure, they may, however, be equally influenced by the expected gains, i.e., turnover in office may be facilitated by the opportunities presented in political afterlife.…”
mentioning
confidence: 99%